Utilização de peptídeos sintéticos derivados das moléculas de Der p 2 e Der p 23 do ácaro Dermatophagoides pteronyssinus para a detecção de anticorpos IgG4 em pacientes com alergia respiratória - Zafalon, Isabella Vilas Boas (2017)
Allergies affect about 30% of the world's population and it has major impacts on health systems, the world economy and people quality of life. Strategies that induce specific allergen tolerance represent a more effective approach in the allergic diseases treatment. The immunotherapy process involves shifting the Th2 response in allergic patients to a Th1 and/or Treg profile response profile response, where IgG4 antibody have a relevant role, disrupting the presentation of antigens mediated by FcRI to Th2 cells and blocking the activation of basophils and mast cells induced by allergens, reducing the allergic response. In this study, we designed and evaluated two synthetic peptides derived from the Dermatophagoides pteronyssinus (Dpt) major allergens, Der p 2 and Der p 23, for detection IgG4 antibodies in allergic patients. The IgE and IgG4 levels in 55 serum samples were evaluated by ELISA. The reactivity analyze to Dpt-extract showed 100% and 84.1% of positivity for IgE and IgG4 in serum samples of allergic patients. From 37 allergic patients producing Dpt-specific IgG4, 48.6% of the serum samples were positive for Der p 2 peptide and 24.3% were positive for Der p23 peptides. A positive correlation was observed between IgG4 to Dpt and IgG4 to Der p 2 (p< 0.001), but no correlation was detected when IgG4 were analyzed in parallel with Dpt versus Der p 23 or Der p 2 versus Der p 23. We observed that serum samples with high IgE:IgG4 ratios to Dpt extract, were also positive to Der p 2 and Der p 23 peptides, indicating that the peptides may be employed in IgG4 detection by indirect ELISA. Thus, the peptides designed in the present study could be potentially useful to monitoring IgG4 levels during AIT protocols and predicting its efficacy.